Academic Achievement, Enthusiasm and Attitude of High School Students Regarding Quizizz as an Educational Gamification Tool for Physics - Nursyahirah Nordin; Ku Siti Syahidah Ku Mohd Noh; A’bir Wardati Abd.Latif; Siti Aisyah Zawawi; Nor Fadzilah Arom Karoman; Haslinawati Mohd Mustapha; Nadiah Kamaruzaman (RSIS International, 2026)
Tier 2 (Indexed by WOS/Scopus/ERA/MyCite)